Measurement accuracy of different active tracking sequences for interventional MRI. Issue 2 (31st October 2013) - Wech, Tobias; Shea, Steven M.; Barbot, Julien; Vij, Kamal; Pan, Li; Lorenz, Christine H.; Patil, Sunil
<x xml:space="preserve">Abstract</x> Purpose To compare the spatial accuracy of three typical active tracking sequences using a new, unique phantom design. Materials and Methods Three different tracking sequences (Single Echo, Dual Echo and Hadamard Multiplexed) were compared with each other in a phantom study with respect to their positional accuracy. A custom‐built phantom was constructed to conduct the experiments with precise framework conditions which facilitated sufficient measurement accuracy. An electrophysiology catheter incorporating four micro‐coils was used as an interventional device. Tracking profiles were acquired in all three spatial dimensions and validated against the distances that were measured by a Vernier caliper in combination with a three‐dimensional reference scan. Results The Bland‐Altman plots demonstrated that all three sequences show < 1.5 mm positional error. The measurement accuracy of Single Echo and Double Echo are prone to off‐resonances, whereas Hadamard Encoding is immune to it. Conclusion The developed phantom enabled the performance of objective measurements of the accuracy of different active tracking sequences. The proposed setup allows for objectively contrasting different methods for interventional procedures. J. Magn. Reson. Imaging 2014;40:490–495. © 2013 Wiley Periodicals, Inc.